Trend and Positioning of Global Top One Hundred Brands - Chen, Rain; Chang, Jo-Han; Chen, Hung-Yuan (Journal of Asian Business Strategy, 2018)
This study applied 173 figurative marks from global top 100 brands from 2006 to 2015 as the objects. The brand distinctiveness test was implemented to 60 general consumers. The Multidimensional Scaling was applied in order to get the similarity of the eight majors industries from the participants. The researcher further established the Two-dimensional Brand Positioning Map (BPM) in order to help the enterprises making brand strategy. The BPM may assist the managers observing the brand positioning of their own enterprises. From the developing trend of the brands of each year, the brand competitive stress of their own enterprises can be observed. The study found that: for the global top one hundred brands, they have excellent distinctiveness to the consumers. In the future, enterprises may apply this approach of analysis to establish their own BPM in order to recognize the trend and positioning of their own brands in the corresponding industries.